Health Care in the Information Society Volume 2 - From Anarchy of Transition to Programme for Reform - Ingram, David (Open Book Publishers, 2023)
In this fascinating book David Ingram traces the history of information technology and health informatics from its pioneers in the middle of the twentieth century to its latest developments. The book is distinctive in its broad scope and coverage and as the eyewitness account of an author who became the first UK professor appointed with the mission to bridge information technology with everyday medicine, health, and care. In this role, he has been a co-founder and leader of two rapidly growing initiatives, openEHR and OpenEyes, which stem from international collaborations of universities, health services and industries. These open source and open platform technologies have struck a widely resonant chord worldwide through their focus on community interest endeavours and open access to their methods and outputs. Set against the history of extremely costly, burdensome, and serially unsuccessful top-down attempts of governments to tackle the domain, the book argues for a greater focus on shared endeavours of this kind, contributing towards a standardized care information utility that incorporates methods and resources evolved, shared, and sustained in the public domain. As information technologies are now at the very core of health care, shaping the relationship between medical services and communities, professions, organisations and industries this book is important reading for politicians, health care academics, administrators and providers, and to anybody interested in the future of health services in the digital age.